First record of Trichotrombidium muscarum (Riley, 1878) (Trombidiformes: Microtrombidiidae) in South America, with morphometric data and host association - Bianca P. Valério; Leopoldo F.O. Bernardi; Livia M. S. Ataide; Ricardo Bassini-Silva (Entomological Communications)
The genus Trichotrombidium Kobulej, 1951 (Microtrombidiidae) includes ectoparasitic mites associated with dipteran species. However, their life cycle remains poorly understood, as only immature stages have been described. In this study, we report the first record of Trichotrombidium muscarum (Riley, 1878) in South America, specifically in Brazil, parasitizing the stable fly, Stomoxys calcitrans (L., 1758) (Diptera: Muscidae). The mites were collected using a pan- trap near a poultry farm in Nepomuceno, Minas Gerais State, Brazil. Morphometric data are provided, expanding the knowledge of this species.